2000
DOI: 10.1073/pnas.260502597
|View full text |Cite
|
Sign up to set email alerts
|

A kinetically significant intermediate in the folding of barnase

Abstract: O ne fundamental question about the pathway of protein folding is whether or not there are folding intermediates; that is, whether a pathway is two-state or multistate. The next question is whether intermediates are on-pathway, that is, on the route between the denatured state, D, and the native state, N. Unequivocal proof of mechanism by kinetics is often neither simple nor straightforward because much of kinetic evidence is by its very nature indirect and hence ambiguous. But the kineticist has two powerful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
102
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 44 publications
13
102
0
Order By: Relevance
“…The first evidence for a folding intermediate came from a roll-over effect in the chevron plot [20]. More recently, analysis of pulse labeling hydrogen exchange protection factors has shown that the intermediate is an on-pathway species to the native state [54]. The structural features of the barnase folding intermediate has been addressed both experimentally (e.g.…”
Section: Structural Features Of Protein Folding Intermediatesmentioning
confidence: 99%
“…The first evidence for a folding intermediate came from a roll-over effect in the chevron plot [20]. More recently, analysis of pulse labeling hydrogen exchange protection factors has shown that the intermediate is an on-pathway species to the native state [54]. The structural features of the barnase folding intermediate has been addressed both experimentally (e.g.…”
Section: Structural Features Of Protein Folding Intermediatesmentioning
confidence: 99%
“…Although some small proteins are thought to fold by a 2-state mechanism in which the unfolded state transitions in a highly cooperative manner to the folded conformer [20] (Figure 1a), it is becoming increasingly clear that for many proteins, folding involves the formation of one or more transiently formed intermediates [1,[6][7][8][9][10]21] (Figure 1b). Sufficiently stable intermediates can be detected kinetically using stop-flow or continuous-flow techniques and proven to be onpathway by kinetic modeling [8,9,22] be populated to a level that is detectable at equilibrium by thermodynamic experiments, and in amenable cases be proven to be on-pathway by relaxation dispersion NMR, a technique which will be described in detail in later sections.…”
Section: Transiently Formed On-pathway Intermediates In Protein Foldingmentioning
confidence: 99%
“…NOESY experiments exploit the phenomenon of cross-relaxation between hydrogen atoms that are close in space. Cross-peaks are generally visible between atoms that are separated by less than 6Å, and their intensity is proportional to 1/r 6 Chapter 2…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…All of the folding limbs for the fast phase converge at ∼3 × 10 5 s −1 . The slow phases exhibited rollover, characteristic of multistate kinetics (12)(13)(14).The dependence of the logarithms of the relaxation rate constants λ on [Urea] were fitted simultaneously assuming that each phase was two-state and each individual rate constant (k) had the standard linear dependence on [Urea], k ¼ k 0 expðm½urea ∕RTÞ, (Fig. 3).…”
mentioning
confidence: 99%